2022
DOI: 10.3390/bios12100897
|View full text |Cite
|
Sign up to set email alerts
|

A High-Performance Self-Supporting Electrochemical Biosensor to Detect Aflatoxin B1

Abstract: High-performance electrochemical biosensors for the rapid detection of aflatoxin B1 (AFB1) are urgently required in the food industry. Herein, a multi-scaled electrochemical biosensor was fabricated by assembling carboxylated polystyrene nanospheres, an aptamer and horseradish peroxidase into a free-standing carbon nanofiber/carbon felt support. The resulting electrochemical biosensor possessed an exceptional performance, owing to the unique structures as well as the synergistic effects of the components. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…mercury, lead, cadmium, and arsenic) are known to pose a serious threat to food safety if consumed above the weekly allowable intake. [ 154 ] developed a cell-free paper-based biosensor for on-site detection of Hg 2+ and Pb 2+ in water using a combination of in vitro transcription (IVT) technology with allosteric transcription factors (aTFs). The detection principle mainly relied on the aTFs specific affinity characteristic toward metal ions that cause dissociation from DNA and result in a measurable signal of transcribed fluorescent RNA ( Figure 9 ).…”
Section: Biosensors In Food Safety and Securitymentioning
confidence: 99%
See 2 more Smart Citations
“…mercury, lead, cadmium, and arsenic) are known to pose a serious threat to food safety if consumed above the weekly allowable intake. [ 154 ] developed a cell-free paper-based biosensor for on-site detection of Hg 2+ and Pb 2+ in water using a combination of in vitro transcription (IVT) technology with allosteric transcription factors (aTFs). The detection principle mainly relied on the aTFs specific affinity characteristic toward metal ions that cause dissociation from DNA and result in a measurable signal of transcribed fluorescent RNA ( Figure 9 ).…”
Section: Biosensors In Food Safety and Securitymentioning
confidence: 99%
“… Schematic diagram of a cell-free paper-based biosensor for on-site detection of heavy metals Hg 2+ and Pb 2+ in water based on aTfs. Reprinted from [ 154 ] with permission from Elsevier. …”
Section: Biosensors In Food Safety and Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Y. Zhang et al [120], using an electrochemical biosensor based on carboxylated polystyrene nanospheres, an aptamer, and horseradish peroxidase assembled on a carbon nanofiber/carbon felt support for the determination of aflatoxin B1, found that after four weeks, recovery rates were reduced by 10.4% (Figure 11).…”
Section: Stability and Response Time Of Biosensorsmentioning
confidence: 99%
“…Y. Zhang et al [120], using an electrochemical biosensor based on carboxylated polystyrene nanospheres, an aptamer, and horseradish peroxidase assembled on a carbon nanofiber/carbon felt support for the determination of aflatoxin B1, found that after four weeks, recovery rates were reduced by 10.4% (Figure 11). Zhao et al, building an evanescent optical fiber aptasensor, checked the reproducibility in 35 cycles that included the sequential injections of the blank (copy DNA only), 0.5% sodium dodecyl sulfate (regeneration buffer at 1.9 pH value), and toxin sample (1 pM ZEN and copy DNA).…”
Section: Stability and Response Time Of Biosensorsmentioning
confidence: 99%